Ochrona praw mniejszości narodowych w orzecznictwie Europejskiego Trybunału Praw Człowieka oraz Komitetu Praw Człowieka ONZ – analiza porównawcza: [Protection of the national minorities – a comparative analysis of the European Court of Human Rights and the UN Human Rights Committee case law] (Studia Prawnicze / The Legal Studies, 2014)
Europejski Trybunał Praw Człowieka (dalej ETPCz lub Trybunał) oraz Komitet Praw Człowieka ONZ (dalej KPCz lub Komitet) orzekają w sprawie skarg indywidualnych zarzucających naruszenie przez państwa odpowiednio Europejskiej Konwencji Praw Człowieka oraz Międzynarodowego Paktu Praw Obywatelskich i Politycznych. Zakres przedmiotowy skarg obejmuje m.in. naruszenia praw osób należących do mniejszości narodowych. Celem niniejszego artykułu jest analiza porównawcza wyroków ETPCz oraz decyzji KPCz dotyczących praw mniejszości narodowych. Prezentacja całości orzecznictwa wykracza niewątpliwie poza objętość jednego artykułu. Z uwagi na wagę poruszanej problematyki analiza została zawężona do trzech wybranych tematów: pisowni imion i nazwisk, edukacji oraz udziału w życiu politycznym. The article analyses case law concerning national minority protection in the jurisprudence of the European Court of Human Rights and UN Human Rights Committee. The protection of national minorities is realized through protecting individual right of persons belonging to minorities. Due to significant amount of cases and given the importance of discussed issues, the analysis is restricted to three topics: names, education and political participation. The case law has set some important standards in those areas. In most of the analyzed aspects the approach of both organs has been the same, for example in regard to names and surnames of persons belonging to national minorities. The research also showed areas in which the case law was not consistent – while examining cases concerning the same French law regarding wearing of religious clothing by students in state schools, the UN Committee, contrary to the Court, found a violation by the state. However, in the vast majority of studied subjects, the jurisprudence of the Court and Committee is very similar and allows to formulate an international standard of national minority protection. Among national minorities indigenous people enjoy in some aspects greater protection than other groups, which is particularly evident in the Committee decisions.